A Case of Disseminated Hypopigmented Keratoses Improved with Oral Acitretin - Ali Haydar Eskiocak; Cumhur İbrahim Bassorgun; Sarp Uzun; Soner Uzun (Case Reports in Dermatological Medicine)
Disseminated hypopigmented keratosis is a distinct clinical entity and only few cases have been reported so far. Here, we present a 21-year-old man with almost 10-year history of hypopigmented, nonfollicular, keratotic lichenoid papules occurring on the extensor surfaces of the extremities, back and lumber region. Histopathological examination showed orthohyperkeratosis, irregular acanthosis, and sporadic papillomatosis with a normal amount of melanin and number of melanocytes. In addition, no marked inflammation or melanophages were seen. In order to exclude other possible causes, we performed laboratory tests and radiological examination which were all found to be normal. As the clinical and histopathological features of our patient were taken into account, it was considered to be compatible with the diagnosis of disseminated hypopigmented keratoses. So far, only topical therapies have been used with failure in the previously reported cases except one patient. Considering the extensive lesions, we treated the present patient with 5% salicylic acid in addition to oral acitretin and significant regression in all lesions was achieved, particularly on the keratosis.